Substitusi Tepung Ikan Teri (Stolephorus sp.) dalam Pembuatan Kue Semprong sebagai Sumber Kalsium untuk Anak Sekolah: Anchovy Substitution on Semprong Cake as Source of Calcium for Children - Adlina Dhiyaul Haq; Nani Ratnaningsih; Badraningsih Lastariwati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
One of the food sources of calcium needed by children is anchovy, but its use in traditional food products is still limited. Semprong cake has the potential as a traditional food that is functional. This study was aimed to determine the formulation of semprong cake with anchovy flour substitution, level of preference and nutritional content with proximate and calcium tests. The research was consist of 4 stages, namely define to find a reference recipe for semprong cake. Design stage by developing selected reference recipes with the substitution of field anchovy flour as much as 5%, 10%, and 15%. In the Development phase, validity tests were carried out on food and nutrition expert lecturers and designing the semprong anchovy cake packaging. Disseminate stage to test product preferences by 100 panelists from school children. The best substitution of anchovy flour on semprong cake is 15%. The preference test for the reference product is 4.0 (preferred) and the development product is 4.9 (strongly preferred). The nutritional content of the Medan anchovy semprong cake consists of 10.77 g protein, 26.49 g fat, 57.04 g carbohydrates, and 486.65 kcal/100 g of product energy. Medan anchovy semprong cake can be categorized as a calcium source snack because it contains 820.63 mg/100 g of calcium. Therefore, the Medan anchovy semprong cake can be recommended as a snack for school children.